Nanotechnology: health and environmental risks of nanomaterials. Research strategy (Dortmund, 2007)
"While reports on nanotechnology by research and marketing firms as well as governmental agencies are comprehensive and insightful, they can often be tedious to read, expensive to procure, and generally unknown to nonexperts interested in this technology. Offering a reader-friendly and affordable alternative to these options, Nanotechnology: Health and Environmental Risks introduces risk analysis as a tool for responsible environmental decision making in nanotechnology development and provides examples of past, present, and future technologies that demonstrate the need for and benefits of evaluating the risks of nanotechnology."